Effect of extrinsic information feedback on motor learning in springboard diving - Cao, C.-M.; Li, C.-W. (Journal of Beijing Sport University, 2017)
The purposes of this study were to analyze whether extrinsic information feedback could promote the training efficiency on takeoff height of springboard diving, and to find a better training method to improve diving skill of young drivers. Methods: Twenty provincial drivers ( 10 male) took part in this study, they were divided into control group ( n = 10) and experiment group ( n = 10) , and finished the same 12 weeks training except that athletes of experiment group had feedback of takeoff height from auxiliary training platform after each training session. Results: 1) Extrinsic information feedback can improve the training efficiency on takeoff height in springboard diving. It promotes the efficiency of athletes to learn new and old movements, and it is more obvious in new movement learning. 2) The analysis of take-off model showed that improving the skill stability of athletes is one of the means to improve training efficiency though external information feedback. 3) The relationship between the depth of springboard and the height of the take-off is not close; the larger depth of springboard cannot guarantee a higher take-off height for athletes.